Correlating damage condition with historical seismic activity in underground sepulchral monuments of Cyprus - Kyriakides, Nicholas; Lysandrou, Vasiliki; Agapiou, Athos; Illampas, Rogiros; Charalambous, Eleftherios (My University, 2017)
Severe and repeated earthquakes devastated Cyprus in antiquity, causing in many cases the abandonment of entire settlement sites. Yet, information regarding the level of seismic activity of historical seismicity in Cyprus is very limited and does not provide the evidence to arrive at reliable conclusions relative to hazard damage parameters such as the severity or occurrence frequency of a seismic event. Thereafter, the level of risk in which these monuments are exposed is unclear leading to an increased uncertainty regarding their safeguarding from future events. The paper aims at investigating the correlation between damage observed in underground ancient tombs and the historical seismic activity at the area based on in situ observations and expert opinion analysis. In addition, the paper aims to simulate the current state of the tomb's structure, and predict, through a seismic scenario, the propagation of damage from future large earthquake events. Underground monuments are chosen since, due to the nature of the seismic force, they are further “protected” and capable of surviving strong ground motions as they follow the displacement of the soil surrounding them. Typical examples of such structures in Cyprus are the hypogea in the necropolis of the “Tombs of the Kings”, located in Paphos area. Some of these monuments exhibit severe cracking of the rock-cut stone walls and evidence of collapse of vertical resisting members of skeleton structure. Paphos area is the most active seismic region in Cyprus based on the historical catalogue of events with evidence of a number of destructive earthquakes. The framework presented herein utilizes information regarding the current geometry of these structures as documented from topographical surveys, their depth, area of opening, size of resisting members along with information regarding the geotechnical conditions at the site to arrive at estimates of the displacement demand under various seismic scenarios. The predicted shear strain levels on the walls are compared with the strain capacity under tension of the soil material to identify the possibility of propagation of cracking of the walls based on a specific seismic scenario.
Keywords: Historic seismic activity; Underground tombs; Ancient earthquakes; Finite element model; Cyprus